Implementation of the Smart Indonesia Program in Order to Improve the Quality of Education at Madrasah Aliyah Ma'had Al-Zaytun - Agustiningsih, Puji; Rosnidah, Ida; Prayitno, Arief (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
The Smart Indonesia Program, hereinafter referred to as PIP, is a government cash transfer provided to students whose parents are not and/or less able to afford their education, as a continuation and expansion of the target of the Poor Student Assistance (BSM) program. Problems in implementing the Smart Indonesia Program include disbursement that is too slow so that there are students who have graduated from school and returned to their homes spread across several provinces cannot disburse aid funds, lack of understanding from parents and the PIP disbursement process that requires students to come to the distribution bank resulting in many students permitting and disrupting the learning process. The research was conducted at Madrasah Aliyah Ma'had Al-Zaytun in Agntar District, Indramayu Regency. The purpose of this study is to analyze the Implementation of the Smart Indonesia Program, supporting and inhibiting factors and solutions using the theory of Merilee S. Grindle Implementation. The method used in this study is a descriptive qualitative method. Data were obtained from interviews with the Head of Madrasah, Maadrasah Operator/Treasurer and PIP recipient students. Based on the research results, the implementation of the Smart Indonesia Program in order to improve the quality of education at Madrasah Aliyah Ma'had Al-Zaytun has been optimal so that it can improve the quality of education.